Ghrelin controls hippocampal spine synapse density and memory performance - Diano, Sabrina; Farr, Susan A; Benoit, Stephen C; McNay, Ewan C; da Silva, Ivaldo; Horvath, Balazs; Gaskin, F Spencer; Nonaka, Naoko; Jaeger, Laura B; Banks, William A; Morley, John E; Pinto, Shirly; et al. (Nature neuroscience, 2006)
The gut hormone and neuropeptide ghrelin affects energy balance and growth hormone release through hypothalamic action that involves synaptic plasticity in the melanocortin system. Ghrelin binding is also present in other brain areas, including the telencephalon, where its function remains elusive. Here we report that circulating ghrelin enters the hippocampus and binds to neurons of the hippocampal formation, where it promotes dendritic spine synapse formation and generation of long-term potentiation. These ghrelin-induced synaptic changes are paralleled by enhanced spatial learning and memory. Targeted disruption of the gene that encodes ghrelin resulted in decreased numbers of spine synapses in the CA1 region and impaired performance of mice in behavioral memory testing, both of which were rapidly reversed by ghrelin administration. Our observations reveal an endogenous function of ghrelin that links metabolic control with higher brain functions and suggest novel therapeutic strategies to enhance learning and memory processes.